MSAP Marker Based Epigenetic Regulation in Symptomatic and Asymptomatic Floral Malady of Soybean (Glycine max) - Snehal Krishna Kad; Pravin VishwanathraoJadhav; Pranita Prabhakar Thakur; Prashant Bhaskar Kale; Sayali Ganesh Magar; Mangesh Pradeep Moharil; Sanjay Bapuji Sakhare; Shyamsundar Shioram Mane; Rameshwar Baliram Ghorade; Raviprakash Govindrao Dani (Brazilian Archives of Biology and Technology, 2022)
Abstract: It has learned that soybean is being affected by a floral disorder known as floral malady where plants fail to develop pod and do notattendfull maturity. For this floral disorder, we present a new methylation-sensitive amplified polymorphism (MSAP) approach for the evaluation of relative quantitative characteristics of non-methylation, hyper-methylation, hemi-methylation, and full methylation status of CCGG sequences, which are recognized by the isoschizomers HpaII and MspI. We applied a technique to analyze alterations in the cytosine methylation a popular Indian soybean (Glycine max L.) genotype, JS-335.The result revealed that in the symptomatic plant, out of 392 MSAP sites, 281 (71.68%), 33 (8.41%),38 (9.69%), and 40(10.20%) found to beun-methylated, hemi-methylated, fully methylated and hyper-methylated, respectively. Whereas, the MSAP profile of asymptomatic plants revealedout of 402MSAP sites, 330 (81.28%) was un-methylated, 22(5.41%) hemi-methylated,29(7.14%) fully methylatedand 25 (6.15%) hypermethylated. In comparison with asymptomatic(18.71%) plant, approximately 10% increased methylation was noted in symptomatic(28.31%) plantprofiles. The increased levels of methylation was recorded in the symptomatic plants about 28.31%and18.71% in asymptomatic. The study showed a higher epigenetic influence on JS-335 genotype of floral malady symptomatic than same genotype of asymptomatic plant. No pod formation in symptomatic plant induce genome wide changes either in promoter or coding region of gene(s) and DNA fragments showing polymorphism related to differences in pattern and extent of methylation associated with floral malady.